ANALISIS KESULITAN SISWA SMP PADA MATERI BANGUN RUANG SISI LENGKUNG - Widya Ayu Agustini; Nelly Fitriani (IKIP Siliwangi, 2021)
This study aims to analyze the difficulties of junior high school students with curved side building materials. This study used a qualitative descriptive method and the subject was the students of Al-Mujahidin Middle School in Karawang, class IX, which numbered 20 students. Then the data collection used was to provide 5 questions of the instrument to students. The analysis technique consisted of assessing the students' answers based on the tests that were distributed, determining the types of errors in answering by students and knowing the many types of student errors. From the results of the research data analysis showed that students were not able to calculate the volume, identify the information included in the questions, and could not solve the material questions in the curved side space. So it can be concluded that students still have not mastered the concept of curved side spaces